Integrated service resource reservation using queueing networks theory. Issue 1 (1st March 2014) - Brewka, Lukasz; Iversen, Villy Baek; Kardaras, Georgios
Abstract : This study analyses multi‐server multi‐service queueing networks with service protection. To guarantee each service a certain quality‐of‐service and at the same time ensure high utilisation of servers, a minimum capacity is reserved each service. In addition, all services share the remaining non‐reserved capacity and all buffers in such a way that the system becomes reversible. This implies the model has product form between nodes and is insensitive to the packet size distribution. An analytical model and algorithm for performance evaluation are presented.